Development of Learning Tools Based on Discovery Learning Models Combined with Cognitive Conflict Approaches to Improve Students' Critical Thinking Ability - Sriatun Andayani (Postgraduate, University of Mataram, 2020)
Critical thinking is an important skill that needs to be developed in students, including vocational high school students. The critical thinking skills of students who are well facilitated in the learning process will be very useful for students' future. This study aims to develop and implement learning tools that combine discovery learning models with cognitive conflict approaches so that they have a good impact on students' critical thinking skills on heat material. The development of this learning tool adapted the 4D model which consisted of define, design, develop, and disseminate. The learning tools are in the form of syllabus, lesson plans, student worksheets, and evaluation instruments in the form of descriptions to measure students' critical thinking skills. This research was carried out at Mataram State Vocational High School 4 in the academic year 2018/2019. The results showed that this learning device obtained a very high level of validity based on an assessment by an expert validator and obtained a high level of practicality based on observations of the implementation of learning and the results of filling out the questionnaire by students. Students' critical thinking skills are also classified as high criteria based on the measurement results of the evaluation of learning. It can be concluded that the developed learning device is valid, practical, and has a good impact on students' critical thinking skills